Kekuatan Pembuktian Wasiat Di Bawah Tangan dan Ratio Legis Putusan Pengadilan Negeri Bitung Nomor 43/Pdt.G/2015/PN.Bit. tentang Jual Beli Tanpa Adanya Bukti Tertulis - Damopolii, Inca Nadya; Sjafi’i, R. Imam Rahmat (Universitas Negeri Malang, 2020)
This study aimed to analyze the force of private testament proofing and the judge's consideration in the Bitung District Court Decision Number 43 / Pdt.G / 2015 / PN.Bit. about sale without any written evidence. The study used a normative research method with a statutory approach and a case approach. The results showed the power of private testament regarding the Bitung District Court Decision Number 43 / Pdt.G / 2015 / PN.Bit. is strong, judging from the power of physical evidence, the power of formal evidence, and the power of material evidence. However, the sale carried out between the plaintiff and the defendant which was not in the presence of the Land Deed Official had weak legal force because it was not in accordance with the prevailing laws and regulations. In their legal considerations, judges used the principle of sale customary law only, namely light and cash, and witness testimony de auditu as evidence. This legal consideration was deemed inappropriate because it was against the Basic Agrarian Law and in general the witness testimony de auditu was rejected as evidence.